IMPLEMENTASI FUNGSI MANAJEMEN MASJID LEMBAGA ADDAKWAH DALAM MENINGKATKAN KEMAKMURAN MASJID HAJA ENDANG SUTIJAH DESA SIBOLANGIT - Khair Telaumbanua, Satria Ramadhan; Madya, Efi Brata (Inspiratif Pendidikan, 2023)
This study aims to determine the Implementation of the Management Functions of the Addakwah Institution Mosque in Increasing the Prosperity of the Haja Endang Sutijah Mosque, Sibolangit Village. This research is a descriptive qualitative research, this research is a field research. The data in this study used primary data sources and secondary data sources. Data collection techniques in this study by conducting semi- structured interviews and observation. Data analysis techniques in this study were in the form of data reduction, data presentation, and conclusions. Checking the validity of the data in this study is by using a triangulation technique. The results of this study indicate that the activities carried out at the Haja Endang Sutijah Mosque in Sibolangit Village are under the management of the Addakwah Institute. The management carried out by the Addakwah Institution is linked to the management function as an effort made to regulate the course of the Addakwah Institution program at the Haja Endang Sutijah Mosque, Sibolangit Village so that the prosperity of the mosque can increase as the goals of the Addakwah Institution. So the implementation of the management function of the Addakwah Institute in increasing the prosperity of the Haja Endang Sutijah Mosque, Sibolangit Village, namely by planning, organizing, implementing, and supervising.